Аллельные варианты генов Vrn и темпы развития изогенных линий мягкой пшеницы - Аксентьева, О.А.; Шулик, В.В.; Жмурко, В.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. The molecular biological analysis of VRN genes allelic variants of soft wheat near-isogenic lines and its role in the determination of plant paces development were investigated. Methods. In cultivars Myronovskaya 808 and Olvia isogenic by genes VRN of the paces development control the speed of the transition to earing was determined in the field and pot experiment. The allelic variants of VRN genes were identified by PCR using allele specific primers (Grain Gene Mass Wheat). Results. Both varieties VRN1 and VRN3 isogenic lines passed to earing on 11–25 days earlier than the VRN2 isogenic line. In fast-growing isogenic lines the genotype of two dominant alleles of genes Vrn-A1a (965 bp and 750 bp) and recessive alleles vrn-B1 (1149 bp) and vrn-D1 (997 bp) were identified. Dominant allele Vrn-B1 (709 bp) and recessive allele vrn-A1 (1068 bp) were detected in slow-growing isogenic lines genotype. However, dominant allele Vrn-D1 wasn’t identified. Conclusion. The studied lines differ in speed of transition to earing depending on the allelic variants of VRN genes. Apparently, the soft wheat paces of development are determined in the interaction of VRN genes which is determined by the allelic state.